Kritické myslenie ako dôležitá súčasť kurikulárnej reformy na Slovensku: Skúmanie fenoménu v slovenskej časopiseckej literatúre - Martina Kosturková; Janka Ferencová; Valentína Šuťáková (Karolinum Press, 2018)
The curriculum reform in Slovakia, which was officially put into educational practice of schools by adopting the new Act No. 245/2008 Coll. on Upbringing and Education (The School Act) has also officially created space for the development of critical thinking. Thorough examination is one of the prerequisites for more effective development of the mentioned capability in the educational practices in schools. The review study focuses on specification of the issue in the professional area in Slovakia. The aim is to integrate the hitherto gained knowledge and to analyze the state of the research in 2008−2017 in the Slovak academic journals. The methodology is based on Mareš's advice (2013) on systematic mapping of articles (n = 72) in the areas of critical thinking. However, the most significant shortcoming is considered the absence of empirical and experimental studies in relevant scientific journals. In addition to this, the critical analysis of the articles show that in spite of more than ten years of urging for the development of critical thinking as the capability of the future, its position in the Slovak education system is still peripheral.